Юриспруденція та юридичні заклади Євросоюзу. Термінологічний словник - Бойко, С. В.; Boiko, S. (ЦНТУ, 2020)
Термінологічний словник призначений для самостійної роботи студентів, підготовки до практичних занять і проведення підсумкового контролю з курсу “Юриспруденція та юридичні заклади Євросоюзу“. The terminological dictionary is intended for independent work of students, preparation for practical classes and carrying out final control of the “Jurisprudence and legal institutions of the European Union” course.
Jurisprudence and legal institutions of the European Union. Terminological dictionary
Keywords: термінологічний словник; юриспруденція; юридичні заклади Євросоюзу; рекомендована література; terminological dictionary; jurisprudence; legal institutions of the European Union; recommended literature